PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK- PAIR-SHARE UNTUK MENINGKATKAN PEMAHAMAN KONSEP MASALAH SOSIAL IPS PADA SISWA SEKOLAH DASAR - Dewi, Candra (Premiere Educandum, 2015)
The purpose of this research is: to improve understanding of social problem concept of social studies throughÂ  applying cooperative learning model type think-pair-share in the students of Elementary School. This is classroom action research (CAR) with two cycles performed. Each cycles consist of four steps, there were planning, implementation of action, observation and reflection. The subjects of this research is fourth grade students in Elementary School State 2 Kedungputeri Ngawi. Data collecting techniques in this research was observation, test, interview and documentation. For data analyzing techniques was reducing data, presenting data, and taking research conclusion or verification. The research result can be conclude that there is an improvement understanding of social problem concept of social studies in fourth grade students of Elementary School State 2 Kedungputeri Ngawi. On initial conditions, the class average value is 61,31 by the number of students who complete learned is 11 students (40,74%). In cycle I, the average value is 79,51 with students who complete learned is 22 students (81,48%). In cycle II, the average value is 91,26 with students who complete learned is 25 students (92,59%).Â Keyword: think-pair-share teaching, understanding concept.